Tetracyclines Diminish In Vitro IFN-γ and IL-17-Producing Adaptive and Innate Immune Cells in Multiple Sclerosis - Florou, Despoina T.; Mavropoulos, Athanasios; Dardiotis, Efthymios; Tsimourtou, Vana; Siokas, Vasileios; Aloizou, Athina-Maria; Liaskos, Christos; Tsigalou, Christina; Katsiari, Christina; Sakkas, Lazaros I.; Hadjigeorgiou, Georgios; Bogdanos, Dimitrios P. (Frontiers in Immunology, 2021)
Introduction Limited data from clinical trials in multiple sclerosis (MS) reported that minocycline, a widely used antibiotic belonging to the family of tetracyclines (TCs), exerts a beneficial short-lived clinical effect A similar anti-inflammatory effect of minocycline attributed to a deviation from Th1 to Th2 immune response has been reported in experimental models of MS. Whether such an immunomodulatory mechanism is operated in the human disease remains largely unknown. Aim To assess the in vitro immunomodulatory effect of tetracyclines, and in particular minocycline and doxycycline, in naïve and treated patients with MS. Material and Methods Peripheral blood mononuclear cells from 45 individuals (35 MS patients, amongst which 15 naïve patients and 10 healthy controls, HCs) were cultured with minocycline or doxycycline and conventional stimulants (PMA/Ionomycin or IL-12/IL-18). IFN-γ and IL-17 producing T-, NK- and NKT cells were assessed by flow cytometry. The effect of TCs on cell viability and apoptosis was further assessed by flow cytometry with Annexin V staining. Results Both tetracyclines significantly decreased, in a dose dependent manner, IFN-γ production in NKT and CD4+ T lymphocytes from MS patients (naïve or treated) stimulated with IL-12/IL-18 but did not decrease IFN-γ producing CD8+ T cells from naive MS or treated RRMS patients. They also decreased IL-17+ T and NKT cells following PMA and Ionomycin-stimulation. Tetracyclines did not affect the viability of cell subsets. Conclusion Tetracyclines can in vitro suppress IFN-γ and IL-17- producing cells from MS patients, and this may explain their potential therapeutic effect in vivo.